Mini-invasive reconstruction technique of the bulbomembranous urethra - V. A. Vorobyev (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The paper presents the technique of the reconstruction of the bulbar and membranous urethra in the occurrence of strictures and sphincter-stenosis. The method uses an autologous graft and has potential advantages over the bulboprostatic anastomosis. Objective. To develop a method of helping patients with existing urethral anastomoses, with a damaged neck of the bladder and a risk of subsequent incontinence, wishing to maintain the erectile function. Materials and methods. 35 patients underwent 36 reconstructions of the urethra from August 2013 to July 2017, 11 - after previous urethral plastics, 14 - after prostate surgery (4 - after radical prostatectomy), 7 - suffered from a urethral distraction defect. The age of the patients was 58.17 ± 12.2 years. The median follow-up period was 525 (341; 813) days. The average length of urethral strictures was 15 (10; 15) mm. The average diameter of the urethra in the stricture zone was 1.4 ± 0.56 mm. Reconstruction with the use of a buccal mucosa graft is performed intraurethrally through corpus spongiosum using magnifying optics. Results. The overall efficacy of the primary reconstruction in 35 patients was 94.2 %; the repeated reconstruction in two patients was successful. All patients underwent the comprehensive monitoring of the results, the average follow-up period was 654 days, the average relapse-free period was 447 days. All patients preserved continence and erectile function Conclusion. The proposed technique showed a high efficiency in reconstruction of the bulbar and membranous urethra.